Morphogenesis and reproductive biology of water lily (Nymphaea spp.) - Tincy Tom (Department of plant breeding and genetics, College of horticulture, 2015)
Genus Nymphaea forms a complicated group of aquatic perennials having immense ornamental and medicinal value. Two phenological groups based on flowering viz., diurnals and nocturnals are recognized in this genus. Information on the reproductive biology and developmental features specific to the phenological groups are lacking in this genus. The present study entitled “Morphogenesis and reproductive biology of water lily (Nymphaea spp.)” was taken up in this background in the Department of Plant Breeding and Genetics, College of Horticulture, Vellanikkara, during 2013-2015 for elucidating and comparing the reproductive biology and developmental pattern of leaves, flowers and fruits in day as well as night blooming types of Nymphaea. A survey was conducted in the water lily growing tracts of Thrissur district and 12 accessions were collected. Five among these accessions were selected based on blooming time and seed set for further detailed evaluation. Growth and development pattern of leaves and flowers were observed to be uniform in all the accessions. However, the accessions differed in the number of days taken by the leaf and flower bud to reach the water surface and maturity. The rate of elongation of the petiole was significantly and positively correlated with sunshine hours and maximum temperature. There was no significant correlation between pedicel elongation and weather parameters. The leaves in all the accessions evaluated were simple orbicular with subpeltate lamina which was deeply cleft near to the petiole base. However, there was variability in the colour, margin and tip of the lamina. The night bloomers could be easily distinguished by the sinuately dentate margin and thick prominent veins on the abaxial surface of the lamina. Flowers were pedicellate and complete with all the floral whorls in a spiral fashion on the floral axis. Significant variability in both qualitative and quantitative characters were observed among the accessions for floral characters. The night bloomers differed from the day bloomers in having larger flowers with stamens devoid of appendages. Besides, the sepals were observed to have five to six prominent nerves on both sides. The flower opened in the morning and closed in the evening in day blooming types. In night bloomers the flower opening was in the evening hours and closing in the morning hours. The time of opening and closing further varied with the accessions. The process of opening and closing continued for four days and on the fifth day the flower submerged in water. The anther dehiscence started on the second day of flower opening and it proceeded from the outermost whorl to the inner most whorl of the stamens. The dehiscence was hence completed in two days in day bloomers. However, in night bloomers the stamens of all the whorls dehisced simultaneously on the first day of flower opening. The presence of honey dew like secretion in the stigmatic cup indicated the initiation of stigma receptivity in all the accessions irrespective of blooming time. The receptivity started 14 to15 hours before flower opening and was retained for 34 hours even after flower opening in day bloomers. In night bloomers the onset of receptivity was six to nine hours prior to flower opening and remained receptive only for 16 to 18 hours after flower opening. Stingless bee (Trigona irridipennis), honey bee, house flies, weevils and flower beetles were the major insects visiting the flowers. Cross pollination was the rule in all the accessions due to the protogynous nature of the flower. Fruit set was noticed only in two of the day blooming types evaluated. Fruit was a many seeded dehiscent capsule which developed under water. All the floral whorls were persistent in the mature fruit. It took 20 to 25 days for the fruit to mature. Seeds were arillate with an embryo, two fleshy cotyledons and a mucilaginous covering. Despite being a dicot, the germination was initiated by the emergence of coleoptile. Acid scarification as well as leaching treatment enhanced the speed of germination of the seeds. Bulbils served as the propagules in the non seed forming accessions.